Digitalisasi Sastra Jawa Digitalisasi Sastra Jawa: Implementasi Media Blog untuk Meningkatkan Keterampilan Menulis Cerkak - Dyah Kurniawati Dyah Kurniawati; Darni; Octo Dendy Andriyanto (Kawruh: Journal of Language Education, Literature and Local Culture, 2026)
This study aims to describe the improvement of students’ cerkak (Javanese short story) writing skills and digital literacy through the use of blogs in madrasah enviroment. The research is motivated by low interest in Javanese literature and creative obstacles found in conventional methods. Initial data from 18 students at MTsN Kota Madiun showed sub-optimal results, with only 2 students achieving the "excellent" category, while the majority fell into the "good" (10 students) and "fair" (6 students) categories. A mixed-methods approach was used, combining interviews with writing performance tests on blogs. The results showed a significant transformation; after guidance, 10 students reached the "excellent" category, 7 students were "good," and only 1 student remained "fair." This study concludes that blog media effectively stimulates creativity and substantially improves students' cerkak writing skills compared to conventional methods.